KB MAL Gambaran Pengetahuan Ibu Hamil tentang Kontrasepsi Metode Amenore Laktasi (MAL) Di Klinik Budi Mulia Medika Palembang Tahun 2025 - Leny; Arly Febrianti; Tirta Anggraini (STIKes Budi Mulia Sriwijaya, 2025)
Contraceptive or family planning services are strategic interventions in reducing maternal and child mortality rates, but currently contraceptive and family planning services have not been fully implemented optimally, this can be shown from the 2017 SDKI data on the achievement of family planning participation for all family planning methods, which is 63.6% with modern family planning participants of 57.2%. The family planning program is a form of government effort that includes counseling, protection and assistance as a form of a person's right in a family to control child birth, pregnancy spacing, and the ideal age for childbirth. The purpose of this study was to determine the Description of Pregnant Women's Knowledge about Lactational Amenorrhea Contraception (LAM) at the Budi Mulia Medika Clinic, Palembang in 2025. The research design used was descriptive research. The population in this study were pregnant women who visited the Budi Mulia Clinic, Palembang at the time the study was conducted, totaling 37 people. The sample of this study was taken by non-random sampling with the research sample being the total population, namely pregnant women who visited the Budi Mulia Clinic, Palembang at the time the study was conducted. The data obtained using univariate analysis by looking at the frequency distribution table obtained as many as 9 respondents (24.3%) had good knowledge, 18 respondents (48.7%) had sufficient knowledge, and as many as 10 respondents (27%). had less knowledge about LAM Contraception to be able to provide more information about the benefits and criteria for using the Lactational Amenorrhea Method (LAM) Contraception so that it can be used effectively so that mothers can choose one of the natural contraceptive methods that do not interfere with breastfeeding